2012
DOI: 10.1128/cvi.00487-12
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Characterization of Fasciola hepatica Tegument Protein Extract for Serodiagnosis of Human Fascioliasis

Abstract: Tegument protein extract from Fasciola hepatica adult flukes (FhTA) was obtained and assessed for its potential as a diagnostic agent for the serological detection of human fascioliasis using an indirect enzyme-linked immunosorbent assay (ELISA). In an analysis of sera from 45 patients infected with F. hepatica, sera from 41 patients with other parasitic infections, and sera from 33 healthy controls, the FhTA-ELISA showed sensitivity, specificity, and accuracy of 91.1%, 97.3%, and 95%, respectively. Specific I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 56 publications
0
20
0
5
Order By: Relevance
“…Th2-dominated responses have been observed in F. hepatica infection in mice, humans, and ruminant hosts. Antibody production is dominated by the immunoglobulin G1 isotype (24,41,42). In experimentally infected cattle, IFN-␥ production and cellular proliferation are detected immediately after infection with the F. hepatica antigen.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Th2-dominated responses have been observed in F. hepatica infection in mice, humans, and ruminant hosts. Antibody production is dominated by the immunoglobulin G1 isotype (24,41,42). In experimentally infected cattle, IFN-␥ production and cellular proliferation are detected immediately after infection with the F. hepatica antigen.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, our research group recently demonstrated that FABP is one of the most prominent components of an F. hepatica tegumental coat antigen (FhTg) that was found to be highly reactive with sera from patients with chronic fascioliasis (24). Consistent with these results, the native F. hepatica FABP (Fh12) purified in this study was found to be highly reactive against human sera obtained from patients with chronic fascioliasis and against antisera raised against specific tegumental coat antigens and excretory-secretory products of F. hepatica.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other possible explanations also could be considered, i.e., (i) the persistence of low antibody levels as these persons could have been previously exposed to F. hepatica, although at the time of sample collection they did not have eggs in their feces (we do not know whether these persons lived in regions with endemic fascioliasis prior to sample collection), or (ii) cases of resolved fascioliasis infections (we recorded no history of possible previous treatment with triclabendazole). We further evaluated the falsepositive serum samples with two other ELISA methods that were previously validated in our laboratory, utilizing as antigens recombinant F. hepatica saposin-2 (25) and F. hepatica tegumental proteins (52), which showed diagnostic specificity values greater than 95%. The results from these two additional ELISAs indicated that 5 of the 11 false-positive serum samples (2 samples with schistosomiasis, 1 with paragonimiasis, and 2 with hydatidosis) could be true-positive cases that were misdiagnosed in the microscopic examinations.…”
Section: Discussionmentioning
confidence: 99%
“…Different antigens of Fasciola including somatic, ES, recombinant and tegumental antigens have been used for immunodiagnosis of human or animal fasciolosis (Morales and Espino 2012;Rokni et al 2003;Shafiei et al 2015). The present study was carried out to determine common antigens of F. hepatica and F. gigantica somatic and ES antigens, using rabbit polyclonal antibodies raised against these two sets of antigens.…”
Section: Discussionmentioning
confidence: 99%